Histogenous Hypoxia and Acid Retention in Schizophrenia: Changes in Venous Blood Gas Analysis and SOD in Acute and Stable Schizophrenia Patients - Huang, Xingbing; Lu, Qiu-Ling; Zhu, Xiu-Mei; Zeng, Yi-Bin; Liu, Yun; Hu, Hao-Ying (Frontiers in Psychiatry, 2021)
Background: Oxidative stress may play an important role in the pathogenesis of schizophrenia (SCH), and there is considerable indirect evidence that hypoxia is closely related to SCH, but direct evidence of hypoxia in SCH has never been found. Methods:In this study, superoxide dismutase (SOD), venous blood gas, and Positive and Negative Syndrome Scale (PANSS) were examined in 40 SCH patients and compared with those of 40 healthy controls. The patients were treated with combination of atypical antipsychotics and Ditan Huayu Lishen decoction (a Chinese medicine decoction) and examined in the acute and stable period, respectively. Comparisons of indicators between two groups were performed using an independent-samples t-test, comparison of indicators between the acute and stable periods in the SCH group was performed using paired-samples t-test. Pearson correlation and multiple linear regression analyses were performed to investigate the relationships between the effect indicators. Results: Higher venous pH, PvO2, and fasting blood glucose levels and lower SOD, lactic acid, and PvCO2 levels were found in SCH patients compared with the control group; SOD was negatively correlated with the general psychopathology subscale score (PANSS-G), and PvO2 levels were closely related to venous pH in SCH and related to PvCO2 in the control group. It was also found that SOD activity showed no significant difference in acute and stable period, whereas PvO2 showed a downward trend, and venous pH was decreased significantly after treatment. Both the venous pH and PvO2 were higher in patients with SCH than that in healthy controls. Conclusion: It suggests that histogenous hypoxia and acid retention exist in relation to SCH, and there is an improvement of acid retention and a downward trend in histogenous hypoxia after combination treatment. Venous pH, PvO2, and PvCO2 are trait variables, but not state variables of SCH. The theory of histogenous hypoxia and acid retention can well explain the decrease in pH value and the increase in lactic acid in brain tissue of patients with SCH. Histogenous hypoxia and acid retention closely related to glucose metabolism. So they may play an important role in pathophysiology for SCH.